IbM KELOMPOK PUPUK KOMPOS PEMUDA MANDIRI DI DESA BENGKEL KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - Irianto Irianto; Rusli Amrul (Sekolah Tinggi Ilmu Ekonomi AMM, 2017)
Science and Technology Program for Communities (IbM) Workshop held in village districts Labuapi West Lombok district, in cooperation with two business partners namely the compost